Mild hypothermia therapy alleviates neuronal damage and repairs cerebral ischemia-reperfusion injury through the SIRT1/AMPK pathway: Effect of mild hypothermia therapy on CIRI - Li, Xiaowei; Shang, Ying; Zhao, Xiaobao; Kong, Ming; An, Hui (Cellular and Molecular Biology, 2024)
Cerebrovascular disease, one of the high-risk diseases worldwide, is high in morbidity, disability, mortality, and recurrence rates, which brings many harms to human beings such as physical and mental harm, economic losses, and impairment of social relations. Cerebral ischemia-reperfusion injury (CIRI) is one of the most common pathological manifestations, with mild hypothermia therapy being the most commonly used treatment in clinical practice. In this study, the research team established a CIRI animal model and found that the neuronal apoptosis rate was significantly increased, accompanied by significant ferroptosis, increased inflammation and oxidative stress damage in brain tissue, and obviously inhibited SIRT1/AMPK pathway. However, after mild hypothermia treatment, the pathological changes of CIRI rats were significantly reversed, and the SIRT1/AMPK pathway was reactivated. Therefore, mild hypothermia may achieve the purpose of CIRI repair by activating the SIRT1/AMPK signaling pathway, and targeted regulation of the SIRT1/AMPK signaling pathway may be a research direction for optimizing mild hypothermia therapy or developing new treatment plans for CIRI.